Telaah Kritis Pemikiran Hermeneutika “Double Movement” Fazlur Rahman (1919 - 1988) - Moh. Agus Sifa'; Muhammad Aziz (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, In Islamic studies, hermeneutics is one approach used to understand Islamic teachings other than Philosophy, Linguistics, Sociology, Anthropology, Psychology, Phenomenology, and History. Hermeneutics is increasingly interesting because it has raised the pros and cons of using this approach to the text of the Qur'an. For Muslims, of course the hermeneutic approach is used to better understand the teachings of Islam which are faced with various challenges of the time. Fazlur Rahman is one of the Muslim hermeneut who offers a rational, systematic and comprehensive methodology in understanding the Qur'an so that it will be realized Al-Qur'an shalih li kulli era wa makan. The methodology can be said as an effort to make the Qur'an able to answer current problems and be able to accommodate changes and developments in the times. What is the hermeneutical concept? What is the methodology offered by Fazlur Rahman? What is the influence of the concepts of West Hermeneutics and Classical Mufassirin on the idea of Fazlur Rahman? These questions will be presented by the author. This study concludes; (1) The method of understanding Qur'anic hermeneutics ulumul through a double movement theory offered by Fazlur Rahman has a comprehensive, holistic and contextual interpretation. Where can be used as a basic reference in solving various current problems; (2) Through the double movement theory, it is expected that the teachings of the Qur'an can continue to live throughout the period because they always get the latest understanding and at the same time can avoid excessive and artificial interpretation; (3) A variety of holistic disciplines are needed to get a valid understanding of the Qur'an with the sociohistorical context and then apply it in the present context; (4) The contextualization contained in Fazlurrahman's thinking through the concept of hermeneutical interpretation of the double movement method is able to revive the Qur'anic texts in accordance with the times, even though methodologically the implementation of this method is imperfect and unable to answer all the problems of interpretation for verses verses that do not have a socio-historical background; (5) The positive side of Fazlur Rahman's hermeneutic thinking is his consistency in putting forward moral ideal principles rather than legal-specific contained in the text so that the meaning of the universality of the Qur'an as the Divine Word that applies li kulli zamaan wa makaan remains to be realized; (6) Fazlur Rahman's criticism grew out of the fact that Muslims had closed their scientific cognition all this time. As a result, so far they have been unable to see the horizon of horizons found in the Qur'an